Evaluation of the cost of capital and the discount rate based on the Russian financial statistics - Dmitry S. Voronov; Lyudmila A. Ramenskaya (Journal of New Economy, 2023)
The cost of capital and the discount rate calculated on its basis are the key parameters in the financial modelling and assessment of investment projects’ economic efficiency. Therefore, the method for their evaluation is always a relevant issue for economists and financiers all over the globe. In conditions of unprecedent sanctions pressure this problem has gained special significance for Russian investors, for whom the assets denominated in ‘unfriendly’ currencies have ceased to be risk-free. The study aims to develop an algorithm for evaluating the cost of capital and calculating the discount rate based on ruble-denominated risk-free assets and Russian financial statistics. The methodological basis of the research is the theories of corporate finance and investment project design, as well as the portfolio theory. The statistics of the Russian stock market for 2003–2022 are studied using general scientific (systems analysis and synthesis) and econometric methods, as well as by adopting the Capital Asset Pricing Model (CAPM) and weighted average cost of capital (WACC). The paper suggests and tests a step-by-step algorithm for collecting and processing the Russian financial statistics to calculate the cost of capital and risk premiums to it. The findings prove that unsystematic risks should be assessed separately, rather than within the weighted average cost of capital, as well as propose a determined mechanism for this. The developed method allows avoiding the prohibitively high values of the cost of capital that arise during the use of foreign sources of information.